Reaction of the Small Intestine to Environmental Factors - Barnoev Akhtam Istamovich; Khasanova Dilnoza Akhrorovna (Genius Journals, 2023)
The small intestine, a vital component of the gastrointestinal system, plays a crucial role in nutrient absorption, digestion, and maintaining overall health. This article explores the intricate and dynamic reactions of the small intestine to a myriad of environmental factors. It delves into the multifaceted responses of the small intestine to factors such as dietary choices, microbial influences, pollutants, temperature variations, and psychological stress. Understanding how the small intestine adapts and responds to its surroundings is essential for comprehending its role in health and disease. Through a comprehensive review of current research, this article sheds light on the intricate interplay between the small intestine and its environment, offering valuable insights for both clinicians and researchers
Keywords: Small intestine; Gastrointestinal health; Environmental factors